واقع تطبيق عناصر الإبداع الإداري ومعوقاته لدى إدارات جامعة الأميرة نوره بنت عبدالرحمن من وجهة نظر الإداريات العاملين فيها - الزامل، مها عثمان (جامعة سوهاج - كلية التربية, 2017)
هدفت هذه الدراسة إلى التعرف على واقع تطبيق عناصر الإبداع الإداري والمتمثلة في: الأصالة، الطلاقة، المرونة، المخاطرة، القدرة على التحليل، الحساسية للمشكلات، والخروج عن المألوف لدى إدارات جامعة الأميرة نوره بنت عبد الرحمن، والتعرف على المعوقات التنظيمية والمعوقات الشخصية التي تحد من تطبيق عناصر الإبداع الإداري لدى إدارات جامعة الأميرة نوره بنت عبد الرحمن من وجهة نظر الإداريات العاملين فيها. وقد استخدمت الباحثة المنهج الوصفي، والاستبانة كأداة للدراسة، وشملت عينة الدراسة (123) من الإداريات العاملين في جامعة الأميرة نوره بنت عبد الرحمن. ومن النتائج التي توصلت لها الدراسة أن - أن درجة تطبيق مديرات إدارات جامعة الأميرة نوره بنت عبد الرحمن لعناصر الإبداع الإداري، ومدى توفر عناصر الإبداع الإداري هي درجة كبيرة. وقد احتلت عنصر المرونة العنصر الأعلى في تطبيق جامعة الأميرة نوره بنت عبد الرحمن لعناصر الإبداع الإداري، بينما احتل عنصر الخروج عن المألوف أقل عناصر الإبداع الإداري. وأظهرت الدراسة أن أفراد عينة الدراسة يرون أن هناك معوقات بدرجة متوسطة تواجه مديرات الإدارات في الجامعة في ممارسة الإبداع الإداري، وكانت المعوقات التنظيمية أكثر تأثيا من المعوقات الشخصية.
This study aimed to identify the status of the application of the elements of the administrative creativity of : originality, fluency , flexibility , risk- analysis capability , sensitivity to problems , and out of the ordinary at Princess Noura Bint Abdul Rahman University. departments, and to identify the obstacles Altnzemih personal obstacles that limit applying the elements of management innovation at Princess Noura Bint Abdul Rahman University departments from the viewpoint of administrators its staff. The researcher used the descriptive approach , and the questionnaire as a tool for the study, and the study sample included( 123 ) of the administrators working in Princess Noura Bint Abdul Rahman University. It is the findings of a study that - that the degree of application managers departments Princess Noura Bint Abdul Rahman University. of the elements of the administrative creativity , and the extent of the administrative Anaasralabdaa offers are great degree. Top flexibility component element has been ranked in the application of Princess Noura Bint Abdul Rahman University for administrative elements of creativity, while finished out of the ordinary elements less administrative creativity element. The study showed that the study sample believe that there are obstacles facing moderately directors of departments at the university in the practice of administrative creativity, and organizational obstacles were more Tothia personal obstacle
Keywords: الإبداع الإداري -- جامعة الأميرة نورة بنت عبدالرحمن -- السعودية -- المعوقات التنظيمية -- التخطيط التربوي -- مديرو الإدارات